1987
DOI: 10.1149/1.2100290
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CdS Thin Films Electrodeposited by an Alternating Current Electrolysis Method

Abstract: Cadmium sulfide thin films have been electrodeposited by a method involving the application of a square wave potential to tin oxide electrodes immersed in an electrolyte containing cadmium sulfate and sodium thiosulfate. To elucidate the main electrodic processes that occur during the positive and negative parts of the applied wave, a voltammetric study has been carried out. The morphology and the structural and optical properties of these films are analyzed. Electrical properties before and after annealing ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Stoichiometric CdS is characterized by 77.8% of Cd and 22.2% of S. Therefore, from the results presented in Table 1, it can be concluded that all the preparation methods show about the same excess of S incorporated either by the solvent (DMSO), or as elemental S for the aqueous depositions. These results agree with the EDAX results already published for deposition method I11 (12,16).…”
Section: Cds Characterizationsupporting
confidence: 92%
“…Stoichiometric CdS is characterized by 77.8% of Cd and 22.2% of S. Therefore, from the results presented in Table 1, it can be concluded that all the preparation methods show about the same excess of S incorporated either by the solvent (DMSO), or as elemental S for the aqueous depositions. These results agree with the EDAX results already published for deposition method I11 (12,16).…”
Section: Cds Characterizationsupporting
confidence: 92%
“…Initial experiments focused on examining CdS films formed in a deposition cell similar to that used by Fatas et aZ. [7] We used alternating voltage cycles, and deposition times that had previously been shown by cyclic voltammetry to be sufficient for the electrolytic formation of low concentrations of S2-. [7] The basic setup for these depositions (referred to as BARE-AU), which were performed on a bare gold electrode (i.e., not modified with a S A M or an LB film) is indicated in Table 1 and in Figure 1A.…”
Section: Electrodeposition Of Cdsmentioning
confidence: 99%
“…Electrolysis with a periodically varying current has been used in anodic dissolution, anodizing and corrosion processes [1]; electrodeposition [2,3] heating systems [4,5]; ohmic sterilization [6]; degradation of inorganic and organic pollutants such as NO and naphthalene [7][8][9][10] and in the synthesis and chemical isomerization of metal-organic complexes [11,12]. Recently, alternating current (AC) was used for the electrophoretic deposition (EPD) of biomolecules suspended in aqueous dispersions.…”
Section: Introductionmentioning
confidence: 99%